O05 How does radiographic knee OA impact musculoskeletal aging in midlife? Findings from the Hertfordshire Cohort study. (20th April 2020) - Fuggle, Nicholas R; Clynes, Michael; Laskou, Faidra; Jameson, Karen; Cooper, Cyrus; Dennison, Elaine
Abstract: Background: With an aging population, the burden of musculoskeletal aging in joints, bones and muscles carries with it significant morbidity. Osteoarthritis (OA) is the most common joint condition, and can be defined clinically or radiologically. Musculoskeletal aging in bone and muscle can be assessed through change in body composition, grip strength and physical performance. The aim of this study was to investigate whether a diagnosis of radiological knee OA impacted involution in muscle or bone in the midlife in a group of community-dwelling older adults in the UK. Methods: Our study comprised 220 members of the Hertfordshire Cohort Study (118 males and 102 females), a group of community dwelling older adults in the United Kingdom. Knee radiographs were performed at baseline (1999-2003), with osteoarthritis defined as a Kellgren and Lawrence score ≥2. At baseline and follow-up (2017) questionnaires assessed physical activity and lifestyle factors; JAMAR dynamometry was performed to assess grip strength; 8 foot walk test was performed to assess gait speed and DXA was performed to assess bone mineral density at the hips and body composition. Linear regression was performed to analyse associations in males and females, before and after adjustment for follow-up time, lifestyle factors (including smoking, alcohol consumption, social class, calcium intake and physical activity), anthropometric measures (BMI) and HRT use and age at menopause in women. The development of hand osteoarthritis was adjusted for grip strength outcomes. Results: The mean age of participants at baseline was 65.0 years. Median follow-up was 16.7 years (range 15.0-18.4 years). Knee osteoarthritis was present in 75 (34%) participants. Radiographic knee osteoarthritis status at baseline was significantly associated with grip strength (β=-3.2kg, -5.3 to -1.1, p < 0.01) at follow-up in females but not in males (β=-2.9, -5.8 to 0.1, p = 0.06). No significant associations between radiographic osteoarthritis status at baseline and other measures of sarcopenia (gait speed or lean mass) or bone mineral density were found in either sex. Conclusion: Our findings demonstrate that the presence of knee osteoarthritis in midlife can have a substantial bearing on grip strength in women over 15 years later independent of the presence of hand osteoarthritis. Grip strength has been shown to correlate closely with lower limb strength and so the demonstrated association between grip strength and knee osteoarthritis is representative of a global weakness resulting from the disease. Reduction in grip strength has been associated with an increased risk of morbidity including falls and fractures. Thus, in order to countermand this association, it may be that concerted interventions (including physical therapy, strengthening and surgical intervention) should be recommended for those with knee osteoarthritis at this stage in the lifecourse. Of course, these findings require replication and validation in other cohorts. Disclosures: N.R. Fuggle None. M. Clynes None. F. Laskou None. K. Jameson None. C. Cooper None. E. Dennison None.